Alternatywne koszty ustanowienia rezerwatów przyrody w lasach na przykładzie wybranych nadleśnictw województwa mazowieckiego - Kaliszewski, Adam; Młynarski, Wojciech (Leśne Prace Badawcze, 2014)
The article presents the results of research on the opportunity costs related to establishing nature reserves in four randomly-selected forest districts located in the Mazowieckie Province: Celestynów, Grójec, Płońsk and Zwoleń. Our analysis included calculation of profits forgone by forest districts due to the cessation of timber harvesting in nature reserves and an estimation of work places lost as a result of introduction of new limitations, as well as the expenses incurred by municipalities related to their establishment of forest tax concessions in nature reserves. The establishment of nature reserves incurred losses related to timber harvest of about 246 thousand m 3 during the period of 10 years, which is equivalent to between 4.1% and 19.8% of the planned timber harvest stated in the forest management plans of the studied forest districts. Total opportunity costs were equal to 25.5-27.2 million PLN during these 10 years or 1502-1605 PLN/ha of nature reserve annually. Annual opportunity costs calculated per unit of forest area were equal to 56-60 PLN/ha. The estimated loss in work places was 98.8 working days annually per 1000 ha of forest area in forest districts. Total expenses incurred by municipalities related to establishment of forest tax concessions in nature reserves reached about 18.1 thousand PLN in 2011. The research results show that the economic and social costs of nature protection activities are concentrated in their places of their origin. Those costs are felt the most by the owners of the affected forests and local communities. We recommend that possibilities are explored for the introduction of instruments to allow the mitigation of negative effects resulting from restrictions in forest use. Restructuring of forest and nature protection policy, to take into account the interests of all stakeholders would provide an improved model for the use of these forests.